From Stereotypes to Understanding: A Phenomenological Study of Javanese Students’ Perceptions of Madurese Peers in Islamic Boarding Schools - Wati, Tri Kurnia; Utami, Setyo (Forum Akademisi dan Dosen Peneliti (FAST), 2026)
This study aims to examine Javanese students’ lived experiences in interpreting intercultural interactions with Madurese peers in Islamic boarding schools. A qualitative phenomenological approach was employed to capture the subjective meanings of these experiences. Data were collected through in-depth interviews with two purposively selected Javanese students who engaged in daily interactions with Madurese peers. The data were analyzed using thematic analysis through phenomenological reduction. The findings indicate that participants initially held media-driven stereotypes portraying Madurese students as aggressive and emotionally expressive. However, sustained interaction within the pesantren context led to a gradual shift in perception, with Madurese peers being understood as calm and approachable. Differences in vocal intonation, which initially caused misunderstanding, were later interpreted as culturally shaped communication styles rather than indicators of negative intent. This study underscores that intercultural understanding is constructed through continuous lived experience and plays a crucial role in reducing stereotypes in multicultural educational settings.